Pelatihan Peningkatan Kosa Kata Bahasa Inggris Tingkat Dasar untuk Kelompok Ibu PKK RPTRA Pinang Pola dalam Melakukan Komunikasi yang Sederhana - Riastri Novianita; Athiy Dina Rosihana; Ondy; Bobby Oktavia Yuskar (Assoeltan: Indonesian Journal of Community Research and Engagement, 2024)
This program aims to improve basic English vocabulary and simple communication skills for PKK mothers at RPTRA Pinang Pola, South Jakarta. Given the important role of PKK mothers in families and communities, English language skills are an urgent need, especially in the current era of globalization. The method used is community-based mentoring which is carried out for two months (October-November 2024), with a direct practice approach and interactive discussions. Mentoring is carried out intensively through lectures, discussions, and conversation simulations in small groups, which allows participants to learn in an atmosphere that is supportive and relevant to everyday needs. The results of the program showed a significant increase in basic English vocabulary mastery. The post-test showed an increase in scores of up to 30-40% compared to the pre-test. In addition, participants experienced increased confidence in using English for everyday conversation, with 75% of participants being able to construct simple sentences independently. Feedback from participants also showed that the community-based mentoring method was more effective and comfortable than the formal training method. This program successfully met its main objectives and provided positive impacts that can support the sustainable development of participants' English language skills.